Behavioural determinants impacting the adoption rate of coronary physiology. (1st May 2021) - Demir, Ozan M.; Schrieken, Charlotte; Curio, Jonathan; Rahman, Haseeb
Abstract: Background: Despite international revascularisation guidelines strongly recommending functional assessment of coronary artery stenosis using pressure-wire derived indices, the adoption rate of coronary physiology remains low. Methods: An online questionnaire was designed to evaluate behavioural determinants impacting the adoption rate of coronary physiology. Factor analysis was performed to combine multiple items of a common behavioural domain into one explanatory factor. Regression analysis was performed to evaluate the influence of resulting factors on the variance of the coronary physiology adoption rate. Additionally, the influence of experience, demographics and provider structures was assessed. Results: 104 interventional cardiologists, from 21 countries, completed the questionnaire. Mean adoption rate of coronary physiology was 26.9%. Regression analysis revealed that factors ease-of-use (Coefficient = 0.58, p = 0.01), financial and/or time constraints (Coefficient = −0.22, p = 0.01) and knowledge about guideline recommendations (Coefficient = 0.21, p = 0.06) had the greatest influence on coronary physiology adoption rate variance (R 2 = 0.3, p < 0.001), with ease-of-use and guideline recommendations positively influencing greater uptake and constraints influencing lesser uptake of adoption of coronary physiology. Conclusion: Ease-of-use, financial and/or time constraints, and knowledge about guideline recommendations were the most relevant behavioural factors impacting the adoption rate of coronary physiology. Ease-of-use was identified as the most influential factor, highlighting the importance of cardiac catheterisation laboratory teams being adequately trained to perform coronary physiology assessment seamlessly. Highlights: Despite revascularisation guidelines adoption of coronary physiology remains low. Online questionnaire to determine the behavioural determinants was performed. Most significant factors were ease-of-use, constraints, and guideline knowledge. Ease-of-use had the strongest association to low adoption. Emphasising importance education and seamless laboratories to improving adoption.